Funding policies for HIV and AIDS: time for change. Issue 6900 (7th August 1993) - McCarthy, M; Layzell, S
Abstract : Funding for HIV and AIDS in England has been allocated to regions by a formula based on the number of cases of AIDS and HIV infection and on population size. Regions have distributed the resources directly to hospitals and community services. A survey of staff and managers in North East Thames region showed that funding arrangements have led to unsatisfactory development of services for HIV and AIDS. Firstly, because hospitals are funded according to current numbers of patients services are highly developed at the central London hospitals and underdeveloped in outer districts. Secondly, specialised community care teams have been established rather than integrating care for HIV and AIDS into generic primary care. Thirdly, the information on district of residence of infected patients is inaccurate, limiting allocation of funds according to population needs. Fourthly, prevention of infection has been given far less attention than treatment and care despite the lack of effective treatment. In future allocations for HIV and AIDS should be made to purchasers rather than directly to providers.